Developing E-Pub for Improving the Competence of BIPA (Indonesian Language for Foreign Speakers) Instructor in The Digital Era - Susi Darihastining; Sujinah Sujinah; Umi Nur Qomariyah; Suyoto Suyoto; Chalimah Chalimah (Graduate School of Universitas Negeri Malang, 2022)
Abstract: Efforts to internationalize the Indonesian language have resulted in the establishment of BIPA programs at several Indonesian and foreign universities. There is no doubt that Indonesian exists on the international stage. Numerous universities in Asia and Europe already include Indonesian as a required subject in their curricula. According to researchers' observations of the BIPA program at several universities in Indonesia, there are still numerous shortcomings of a good management system: lecturers' teaching materials do not reflect local culture, teaching strategies are not yet applicable, and media development is less diverse and innovative. The issue at hand is how to use E-PUB media in the digital era to build the capacity of Indonesian language teachers for foreign speakers (BIPA). This research employed a qualitative study with a descriptive approach, thus the data analysis used descriptive statistical analysis. The subjects of this study, or data sources, were LPPI tutors. In BIPA learning, E-PUB applications form data. Data collection methods include observation, interviewing, and documenting. The research findings have resulted in the implementation of E-PUB, which has the potential to increase the professionalism of BIPA tutors.Abstrak: Upaya untuk menginternasionalisasikan Bahasa Indonesia telah menyebabkan adanya pendirian program BIPA pada beberapa universitas di Indonesia dan di universitas di negara-negara asing lainnya. Tidak diragukan lagi bahwa Bahasa Indonesia diakui keberadaannya di kancah internasional. Banyak universitas di Asia dan di Eropa sudah memasukkan Bahasa Indonesia sebagai matakuliah tambahan dalam kurikulum mereka. Berdasarkan observasi para peneliti terdahulu dalam program BIPA di beberapa universitas di Indonesia, masih terdapat banyak variasi kekurangan pada sistem manajemen yang baik: bahan materi ajar oleh dosen tidak merefleksikan budaya lokal, strategi mengajar yang belum diaplikasikan, dan perkembangan media yang kurang variatif dan inovatif. Isu penelitian yang muncul dalam penelitian ini adalah bagaimana menggunakan media E-PUB untuk membangun kapasitas dari guru-guru Bahasa Indonesia yang mengajar penutur asing (BIPA). Penelitian ini menggunakan studi kualitatif dengan pendekatan deskriptif, dengan demikian data analisis menggunakan analisis desckriptif statistikal. Subjek penelitian atau sumber data dalam penelitian ini adalah tutor LPPI. Dalam pembelajaran BIPA, aplikasi E-PUB digunakan untuk mendapatkan data. Metode pengumpulan data menggunakan observasi, interview, dan dokumentasi. Temuan penelitian menunjukkan implementasi E-PUB memiliki potensi meningkatkan tingkat profesionalisme tutor BIPA.